Generalized Anxiety Disorder and Sleep Quality of Day Laborers during COVID-19 Pandemic - Zubayer, Tansiv; Ahmed, Faisal; Ara, Jannat; Mahmood, Maymunah; Rahman Khan, Radaur; Nurunnabi, Mohammad (Medicine Today, 2025)
Introduction: Since December 2019, Coronavirus Disease (COVID-19) has had a significant impact on the world. It had severe economic repercussions in Bangladesh. The lockdown had interfered with the production, availability, and supply of enough food. As a result, food prices have increased, making it harder for low-income individuals, such as day laborers, to survive. Aims and objectives: The purpose of the study was to determine the level of generalized anxiety disorder (GAD) and evaluate the association between sleep quality and GAD among day laborers during the COVID-19 pandemic. Materials and Methods: This cross-sectional study was conducted among 227 construction workers, rickshaw pullers, van pullers, and other day laborers from the Faridpur district. Participants were conveniently selected and interviewed in person using a semi-structured questionnaire, with data collection taking place at their convenience from January to December 2020. Results: The majority of respondents reported minimal anxiety (75.3%), followed by mild anxiety (14.5%), moderate anxiety (9.7%), and severe anxiety (0.4%). most respondents had good sleep quality (74.4%), while 25.6% experienced poor sleep quality. A strong positive correlation was observed between GAD scores and sleep quality scores (p<0.05). A significant association was found between anxiety and sleep quality, with higher levels of anxiety linked to poorer sleep quality. Factors such as age, marital status, smoking, and years of work experience were significantly associated with sleep quality (p<0.05). Unmarried participants were more likely to report poor sleep, potentially due to fewer family-related responsibilities compared to their married counterparts. Conclusion: This study revealed that day laborers during the COVID-19 pandemic had a significant mental health charges. It should be widespread procedure to continuously monitor and assess the psychological effects of the day workers during this period. Medicine Today 2025, Vol.37 (2): 218-224